Comparison of early and late 68Ga-FAPI-46-PET in 33 patients with possible recurrence of pancreatic ductal adenocarcinomas - Hoppner, Jorge; van Genabith, Levin; Hielscher, Thomas; Heger, Ulrike; Sperling, Lucas; Colbatzky, Teresa; Gutjahr, Ewgenija; Lang, Matthias; Pausch, Thomas; Spektor, Anna-Maria; Glatting, Frederik M.; Liermann, Jakob; et al. (Scientific reports, 2023)
Positron emission tomography with 68Gallium (68Ga) labeled inhibitors of fibroblast activation protein (68Ga-FAPI-PET) is a promising imaging technique for patients with recurrent pancreatic ductal adenocarcinomas (PDAC). To date, it is not clear if different acquisition timepoints for 68Ga-FAPI-PET may result in comparable imaging information and if repetitive 68Ga-FAPI-PET imaging may add diagnostic value to single timepoint acquisition for recurrent PDAC. Here we analyzed retrospectively early (20 min p.i.) and late (60 min p.i.) 68Ga-FAPI-PET imaging using FAPI-46 of 33 patients with possible recurrence of PDAC concerning detection rates and uptake over time of local recurrences, metastases, inflammatory lesions of the pancreas, cholestatic lesions of the liver and reactive tissue. 33 patients with histologically confirmed PDAC after complete or partial resection of the pancreas and possible recurrence were examined by 68Ga-FAPI-46-PET acquired 20- and 60-min post injection (p.i.) of the radiotracer. FAPI-positive lesions were classified as local recurrences, metastases, inflammatory lesions of the pancreas (ILP), cholestatic lesions of the liver and reactive tissue based on histology, PET- and CT-morphology and clinical information. Lesions were contoured, and standardized uptake values (SUVmax and SUVmean) and target-to-background ratios (TBR) were analyzed for both acquisition timepoints. In total, 152 FAPI-positive lesions (22 local relapses, 47 metastases, 26 inflammatory lesions of the pancreas, 28 reactive tissues, and 29 cholestatic lesions) were detected. Detection rates for the early and late acquisition of 68Ga-FAPI-46-PET were almost identical except cholestatic lesions, which showed a higher detection rate at early imaging. SUV parameters and TBRs of ILP significantly decreased over time. Cholestatic lesions showed a tendency towards decreasing uptake. All other types of lesions showed relatively stable uptake over time. Early and late acquisition of 68Ga-FAPI-PET results in comparable imaging information in patients with possible recurrence of PDAC. Two timepoint imaging offers additional diagnostic potential concerning differential diagnoses.